Catfish Cultivation with Application of Gravity System Pool Tarpaulin Drain for Fishery Group in Paya Bujok Seuleumak Village, Langsa City - Kartika Aprilia Putri; Fahmy Armanda; Andri Yusman Persada; Suri Purnama Febri; Herlina Putri Endah Sari; Teuku Fadlon Haser; Syahriandi Syahriandi (Fakultas Pertanian, Universitas Samudra, 2023)
The large demand for catfish consumption is the main goal of catfish cultivation in Paya Bujok Seuleumak Village to improve the economy of the village community. The location is also very supportive for fish cultivation because the location distance is not too far from the city and the people are creative in entrepreneurship. The problems that are often faced by cultivator is pond waterflow when entering the rainy season due to an increase in water discharge. This situation caused many fish come out of the pond. Besides, fish feed residue and fish waste can also interfere with pond water quality that trigger many fish die which can cause harvest failure. The solution offered is implementing a gravity system pool tarpaulin drain which can maintain pool water discharge and pool water quality, so that it can keep fish in the pond and stay healthy if there is an increase in pool water discharge. The output target to be achieved are article publication in the National Journal, publication in online and print mass media, products of a gravity system pool tarpaulin drain device and HaKI. There are also additional outputs in the form of increasing fish yields and improving the economy of the communities. The service activity plan consists of coordinating with cultivator, socialization, training on the application of the tarpaulin drain gravity pool system, as well as mentoring and monitoring of the activities carried out.